Dipyridylmethane Ethers as Ligands for Luminescent Ir Complexes - Volpi, Giorgio; Garino, Claudio; Gobetto, Roberto; Nervi, Carlo (Molecules (Basel, Switzerland), 2021)
This work reports two new cationic heteroleptic cyclometalated iridium complexes, containing ether derivatives of di(pyridin-2-yl)methanol. The new ligands are based on dipyridin-2-ylmethane and are designed to obtain ether-based intermediates with extended electronic conjugation by insertion of π system such as phenyl, allyl and ethynyl. Different synthetic strategies were employed to introduce these units, as molecular wires, between the dipyridin-2-ylmethane chelating portion and the terminal N-containing functional group, such as amine and carbamide. The corresponding complexes show luminescence in the blue region of the spectrum, lifetimes between 0.6 and 2.1 μs, high quantum yield and good electrochemical behavior. The computational description (DFT) of the electronic structure highlights the key role of the conjugated π systems on optical and electrochemical properties of the final products.